Association between Vitamin D Deﬁciency and Bacterial Vaginosis among First Trimester Pregnant Women in Erbil Maternity Hospital - Palpitany , Sadiya Abdulla; Alchawshili, Khanzad Hadi; Hassan, Amanj Zrar; Al-Banna, Dara Abdulla (Diyala Journal of Medicine, 2019)
Background: Bacterial vaginosis (BV) is a polymicrobial clinical syndrome characterized by changes in vaginal flora, with replacement of normally abundant Lactobacillus species by high concentrations of anaerobic bacteria among reproductive age women. Studies have different aspects on the effect of vitamin D on BV. Objective: To find out the prevalence of BV, vitamin D deficiency in early pregnancy and to examine association between BV and vitamin D deficiency. Patients and Methods: A cross-sectional study was carried out during July 2017 till October 2018 among 100 pregnant women at first trimester pregnancy, aged 18-35 years old at Erbil Maternity Hospital. Results: At enrollment the prevalence of BV was (53%), about (73%) of our clients suffering from homogenous white greyish vaginal discharge, (57%) were with elevated vaginal PH and fishy odor, clue cells was found among (53%) of them. Vitamin D deficiency, defined as 25 (OH) D concentration below 20 ng/ml, was found in (67%) of women. Insufficiency of the vitamin D 25(OH) D concentration between 20-30ng/ml was present in (29%) of the women. Sufficient level of 25 (OH) over (30 ng/ml) was found in (4%). The incidence of Vitamin D pattern among women with BV were (49.3%), (62.1%) and (50%) respectively for each vitamin D deficiency, Insufficiency and sufficient vitamin D. No significant association was found between Vitamin D deficiency and BV. Conclusion: High occurrence of BV and vitamin D deficiency were found. Vitamin D was not associated significantly with increased BV incidence. We suggested that pregnant women should check and manage their level of vitamin D and BV additionally they must not depend only on vitamin D for curing BV.